2020
DOI: 10.2118/200341-pa
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Oil-Recovery Mechanisms during Natural-Gas Huff ‘n’ Puff Experiments on Ultratight Core Plugs

Abstract: Summary Despite promising natural gas huff ‘n’ puff (HnP) field-pilot results, the dominant oil-recovery mechanisms during this process are poorly understood. We conduct systematic natural-gas (C1 and a mixture of C1/C2 with the molar ratio of 70:30) HnP experiments on an ultratight core plug collected from the Montney tight-oil formation, under reservoir conditions (P = 137.9 bar and T = 50°C). We used a custom-designed visualization cell to experimentally evaluate mechanisms controlling gas tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…However, the overall trend of the pressure profile is still relatively similar to Test 1, since there is a distinguishable pressure drop in the early soaking, followed by a stable pressure profile in the late soaking. Tran et al stated that similar pressure profiles during the soaking period suggest similar solvent transport mechanisms . Therefore, the same conclusion can be made for Test 2 and Test 3 such that advective transport by the pressure gradient dominates the early soaking, whereas diffusive transport by the concentration gradient is responsible for the late soaking.…”
Section: Resultsmentioning
confidence: 74%
“…However, the overall trend of the pressure profile is still relatively similar to Test 1, since there is a distinguishable pressure drop in the early soaking, followed by a stable pressure profile in the late soaking. Tran et al stated that similar pressure profiles during the soaking period suggest similar solvent transport mechanisms . Therefore, the same conclusion can be made for Test 2 and Test 3 such that advective transport by the pressure gradient dominates the early soaking, whereas diffusive transport by the concentration gradient is responsible for the late soaking.…”
Section: Resultsmentioning
confidence: 74%
“…Our previous studies present more detailed properties of these core plugs. 39,40 All core samples and end pieces were aged before conducting the experiments. First, we dried the rock samples in an oven at 90 °C to evaporate the initial oil and water in the pores.…”
Section: Methodsmentioning
confidence: 99%
“…Table lists the core plugs’ mineralogy that is determined by X-ray diffraction (XRD) analysis. Our previous studies present more detailed properties of these core plugs. , …”
Section: Methodsmentioning
confidence: 99%
“…The authors of that study also concluded that the use of methane above its minimum miscibility pressure with the crude oil reduced oil recovery by only 10%. It has also been well established that enriching methane with natural gas liquids in huff 'n' puff could significantly reduce the minimum miscibility pressure and enhance oil extraction (Tran et al 2021). Song et al (2021) conducted huff 'n' puff experiments on Upper Devonian Duvernay core samples and observed that adding propane to the injected mixture of methane and ethane resulted in an increase in oil recovery.…”
Section: Introductionmentioning
confidence: 99%